2022
DOI: 10.1177/10915818221146468
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Hesperidin as an Effective Factor in Initiating the Intrinsic Pathway of Apoptosis in KG1a Leukemia Cells

Abstract: Acute myeloid leukemia (AML) is the most common subtype of leukemia, accounting for 62% of all leukemia fatalities. As a polyphenol glycoside, hesperidin triggers the apoptotic pathway, which might positively affect combating cancer cells. In this study, we investigated the pro-apoptotic effects of hesperidin in KG1a cells. The MTT assay was used to determine the IC50 of hesperidin in KG1a cell lines. For the apoptotic cell morphology study, we used Hoechst 33 258 staining. Activation of the caspase-3 enzyme w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The findings exhibited that hesperidin treatment meaningfully decreased the expression of the antiapoptotic gene, including Bcl2 and survivin, and that treatment significantly increased the expression of the pro-apoptotic genes Bax and the cell cycle regulator p21 compared with the control group. These results indicated that hesperidin may be an effective apoptosis initiator and an appealing option in the therapy of acute myeloid leukemia [ 85 ].…”
Section: Role Of Hesperidin As Both a Cancer Preventative And Curativ...mentioning
confidence: 99%
“…The findings exhibited that hesperidin treatment meaningfully decreased the expression of the antiapoptotic gene, including Bcl2 and survivin, and that treatment significantly increased the expression of the pro-apoptotic genes Bax and the cell cycle regulator p21 compared with the control group. These results indicated that hesperidin may be an effective apoptosis initiator and an appealing option in the therapy of acute myeloid leukemia [ 85 ].…”
Section: Role Of Hesperidin As Both a Cancer Preventative And Curativ...mentioning
confidence: 99%